Team Learning Behaviors and Performance: A Meta-Analysis of Direct Effects and Moderators. Issue 3 (June 2022) - Wiese, Christopher W.; Burke, C. Shawn; Tang, Yichen; Hernandez, Claudia; Howell, Ryan
Under what conditions do team learning behaviors best predict team performance? The current meta-analytic efforts synthesize results from 113 effect sizes and 7758 teams to investigate how different conceptualizations (fundamental, intrateam, and interteam), team characteristics (team size and team familiarity), task characteristics (interdependence, complexity, and type), and methodological characteristics (students vs. nonstudents and measurement choice) affect the relationship between team learning behaviors and team performance. Our results suggest that while different conceptualizations of team learning behaviors independently predict performance, only intrateam learning behaviors uniquely predict performance. A more in-depth investigation into the moderating conditions contradicts the familiar adage of "it depends." The strength of the relationship between intrateam learning behaviors and team performance did not depend on team familiarity, task complexity, or sample type. However, our results suggested this relationship was stronger in larger teams, teams with moderate task interdependence, teams performing project/action tasks, and studies that use measures that capture a wider breadth of the team learning behavior construct space. These efforts suggest that common boundary conditions do not moderate this relationship. Scholars can leverage these results to develop more comprehensive theories addressing the different conceptualizations of team learning behaviors as well as providing clarity on the scenarios where team learning behaviors are most needed. Further, practitioners can use our results to develop more guided team-based policies that can overcome some of the challenges of forming and developing learning teams.